Efficacy of TACE plus tyrosine kinase inhibitors and immune checkpoint inhibitors in patients with unresectable hepatocellular carcinoma: a systematic review and meta-analysis - Ye, Kailin; Zhou, Jiale; Lin, Jie; Li, Yongzhi; Luo, Yansong; Xie, Fei (Frontiers in Oncology, 2025)
BackgroundTransarterial chemoembolization (TACE) is currently widely used in the treatment of patients with unresectable hepatocellular carcinoma. However, the combination of TACE with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) during treatment remains controversial. This study aims to evaluate the efficacy and safety of TACE combined with TKIs and ICIs in patients with unresectable hepatocellular carcinoma and to compare this approach with other treatment regimens.MethodWe conducted a systematic search of relevant studies from multiple online databases, with the search deadline set at March 2025. We explored the relationship between prognosis and adverse reactions of TACE + TKIs + ICIs combination therapy, TACE + TKIs therapy, and TACE monotherapy in patients with unresectable hepatocellular carcinoma. Based on heterogeneity assessment results, we used fixed- or random-effects models and employed trial sequential analysis (TSA) to determine whether the findings have sufficient conclusive power.ResultThis study included 24 cohort studies involving 3,906 patients. Compared with TACE plus TKIs therapy and TACE monotherapy, the combination therapy of TACE plus TKIs plus ICIs significantly improved the objective response rate (ORR) (risk ratio [RR] = 1.49 [95% confidence interval [CI] = 1.35–1.63], p < 0.001 and RR = 1.75 [95% CI 1.48–2.06], p < 0.001), disease control rate (DCR) (RR = 1.27 [95% CI 1.20–1.34], p < 0.001 and RR = 1.39 [95% CI = 1.23–1.58], p < 0.001), and median progression-free survival (mPFS) (mean difference [MD] = 6.05 months [95% CI = 4.77–7.33], p < 0.001 and MD = 7.84 months [95% CI = 5.44–10.24], p < 0.001), and median overall survival (mOS) (MD = 2.93 months [95% CI = 2.57–3.29], p < 0.001 and MD = 4.63 months [95% CI = 2.32–6.95], p < 0.001). TSA confirmed that the current sample size was sufficient to support these conclusions. Univariate and multivariate prognostic analyses indicated that the combination therapy of TACE, TKIs, and ICIs, akin to established clinical factors in hepatocellular carcinoma, can serve as a prognostic assessment indicator for patients with unresectable disease. Although the triple therapy carried a slightly higher risk of adverse events compared with the other two treatments, no grade 5 adverse events were observed, indicating that this regimen was generally well tolerated.ConclusionThis study demonstrates that, compared with TACE combined with TKIs and TACE monotherapy, TACE + TKIs + ICIs combination therapy can substantially improve the prognosis of patients with unresectable hepatocellular carcinoma while maintaining a manageable safety profile. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO CRD420250653604.